TMEPAI increases lysosome stability and promotes autophagy. (July 2016) - Luo, Shenheng; Yang, Meng; Lv, Dan; Jing, Lei; Li, Yuyin; Liu, Zhenxing; Diao, Aipo
Abstract: Autophagy is emerging as a critical response of normal and cancer cells to environmental changes and plays an important role in cell metabolism and maintenance of damaged organelles. Transmembrane prostate androgen-induced protein (TMEPAI) is a pro-tumorigenic factor with high expression in tumor cells. In this study, we showed that depletion of TMEPAI leads to lysosomal labilization and inhibits autophagy. Further study showed that the inhibition of autophagy induced by the depletion of TMEPAI is involved in regulation of Beclin-1. Depletion of TMEPAI increases the sensitivity of cancer cells to chemotherapeutic drugs. Our study reveals the role of TMEPAI in promoting lysosome stability and autophagy, which might be used as a target for cancer chemotherapeutic treatment.